Trends in Class VI Students' Thinking in Understanding Negative Integer Number Through Number Lines - M Qoyum Zuhriawan; M Farid Nasrulloh; Wisnu Siwi Satiti; Fitri Umardiyah (APPLICATION: Applied science in Learning Research, 2023)
One of the prerequisites for students in studying mathematics is to understand integers, both positive and negative integers. But negative integers have significant differences with positive integers. In addition, negative integers are known to have a significant difference with positive integers. Therefore the purpose of this research is to see how students understand negative integers by using a number line. The subjects of this study were class VI students of Madrasah Ibtidaiyah Nurul Hidayah Nganjuk. From this study, it was found that 50% of students described the position of numbers on the number line by sorting them and without writing negative signs. 8% of students describe the position of numbers on the number line with the appropriate concept. 17% of students describe the position of numbers on the number line correctly but ignore the zeros. And as much as 25% of students describe the position of numbers on the number line by only writing positive numbers on the right side.